2013
DOI: 10.4028/www.scientific.net/amr.753-755.1755
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Response Analysis of Lateral-Torsional Coupling Vibration of the Slewing Mechanism of a Hydraulic Excavator

Abstract: A lateral-torsional coupled vibration model of the slewing mechanism of a hydraulic excavator is developed with consideration of the effect of lateral vibration and torsional vibration of sun gear and planetary gear on mesh displacement, the mesh stiffness of gear pairs, the bearing stiffness of the planetary and the coupling relationship of two stage planetary gear trains. The dynamic response of the slewing mechanism of a hydraulic excavator is obtained. Compared to the pure torsional vibration, the lateral-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…at the beginning of design for unload operation [9]; s J , p J and r J are the moments of inertia of sun gear, planet and ring gear, respectively; c J is the equivalent moment of inertia of the carrier which is defined as The Lagrange equations of motion of the (2n+9) degrees of fredom torsional dynamic model of the slewing mechanism as shown in Fig. 1 are given as 0, , , , ,…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…at the beginning of design for unload operation [9]; s J , p J and r J are the moments of inertia of sun gear, planet and ring gear, respectively; c J is the equivalent moment of inertia of the carrier which is defined as The Lagrange equations of motion of the (2n+9) degrees of fredom torsional dynamic model of the slewing mechanism as shown in Fig. 1 are given as 0, , , , ,…”
Section: Modelingmentioning
confidence: 99%
“…( 3), here taking the moment of inertia of the input end for example to illustrate the relation beteen the natural frequencies of the slewing mechanism and its parameters. In fact, the moment of inertia of the input end of the slewing mechanism is varied with the motion of the work equipment, such as the angel of boom 1 β , the angel of arm 2 β and the angel of bucket 3 β [9,10], the main aim of this study focuses on the influence of the variety of moment of inertia of input end owing to the motion of work equipment on the natural frequencies, while the simulation of the moment of inertia of the input end is complex, which can be carried out using the method developed by other scholars [9,10], for simplifcation, here the moment of inertia of the input end varies besides its empirical value, and the relationship between the moment of inertia of the input end and the natural frequencies is obtained as shown in Fig. 2 to Fig.…”
Section: Solutionmentioning
confidence: 99%
“…e result showed that the maximum composite stress in the fatigue failure area under all working conditions decreased from 172.46 MPa to 123.82 MPa. Yang et al [6] established a coupled lateral-torsional vibration model of the rotary mechanism of the hydraulic excavator by considering the rotary platform as an equivalent rotational inertia unit. Jovanović et al [7] developed software to enable the determination and detailed analysis of the slewing bearing load in the entire working range of the excavator.…”
Section: Introductionmentioning
confidence: 99%